Secondary battery, battery device, method for producing modified styrene-butadiene rubber
Patent Information
- Application Number
- CN202510479495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
AI Technical Summary
然而,随着二次电池的应用范围越来越广泛,对二次电池的循环性能也提出了严峻挑战
Smart Images

Figure CN122968282A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to secondary batteries, battery devices, and methods for preparing modified styrene-butadiene rubber. Background Technology
[0002] In recent years, with the increasing maturity of rechargeable batteries, they have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. However, as the application scope of rechargeable batteries becomes wider, serious challenges are also posed to their cycle performance. Currently, there are still many problems to be solved in the actual production and application of lithium-ion rechargeable batteries.
[0003] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention
[0004] In a first aspect, this application proposes a secondary battery comprising: a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative active material layer located on at least one side of the negative current collector, the negative active material layer including a binder, the binder including modified styrene-butadiene rubber, the modified styrene-butadiene rubber having a tensile strength of 3 MPa-8 MPa and an elongation at break of 150%-400%; and an electrolyte having a viscosity of 3 mPa·s-6 mPa·s at 25°C. This can improve the cycle performance of the battery by mitigating the degradation of the electrolyte's wettability on the negative electrode sheet during charging and discharging, thus effectively improving the battery's cycle performance.
[0005] In some embodiments, the modifying groups of the modified styrene-butadiene rubber include one or more of carboxyl, amide, and ester groups. This helps to improve the mechanical strength of the binder and helps resist the stress generated during the expansion and contraction of the negative electrode sheet.
[0006] In some embodiments, the modified styrene-butadiene rubber has a weight-average molecular weight of 20,000-60,000. This results in better dispersion of the binder in the negative electrode sheet and higher mechanical strength.
[0007] In some embodiments, the modified styrene-butadiene rubber has a glass transition temperature of -30°C to -15°C. Therefore, the binder remains in a highly elastic state at the battery operating temperature, which helps to improve the toughness of the negative electrode sheet.
[0008] In some embodiments, the mass fraction of the modified styrene-butadiene rubber in the negative electrode active material layer is 0.5%-2.5%. Therefore, the negative electrode sheet has high structural stability, and the proportion of negative electrode active material in the negative electrode active material layer is relatively high.
[0009] In some embodiments, the modified styrene-butadiene rubber has a swelling rate of 30%-50% in the electrolyte. This helps to improve the wettability of the electrolyte for the negative electrode sheet.
[0010] In some embodiments, the binder further includes a polyacrylic binder, wherein the mass fraction of the polyacrylic binder in the negative electrode active material layer is less than or equal to 1.5%. Thus, adding a small amount of polyacrylic binder helps to provide rigid support and enhance the structural stability of the negative electrode sheet.
[0011] In some embodiments, the negative electrode active material layer further includes carbon nanotubes, wherein the mass fraction of carbon nanotubes in the negative electrode active material layer is 0.01%-0.2%. This improves the conductivity of the negative electrode active material layer while also helping to maintain the pore channels within the negative electrode active material layer, promoting electrolyte reflux.
[0012] In a second aspect of this application, a method for preparing modified styrene-butadiene rubber (SBR) is provided, comprising: mixing 40-60 parts by weight of butadiene, 30-50 parts by weight of styrene, 3-8 parts by weight of acrylate, 1-5 parts by weight of acrylic acid, and 1-5 parts by weight of acrylamide, along with an emulsifier and an initiator, and heating to obtain a polymer emulsion of the modified SBR. This yields a modified SBR adhesive with superior toughness.
[0013] In some embodiments, the modified styrene-butadiene rubber in the polymer emulsion has a Dv50 particle size of 150 nm to 300 nm. This helps to improve the dispersion uniformity of the modified styrene-butadiene rubber.
[0014] In a third aspect, this application proposes an electrical device including the aforementioned secondary battery. Therefore, this electrical device possesses all the features and advantages of the aforementioned secondary battery, which will not be repeated here. Attached Figure Description
[0015] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0016] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application;
[0017] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of this application is shown;
[0018] Figure 3 This is a schematic diagram of a battery module according to an embodiment of this application;
[0019] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application;
[0020] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of this application is shown;
[0021] Figure 6 This is a schematic diagram of an electrical device in which a battery is used as a power source, according to one embodiment of this application.
[0022] Explanation of reference numerals in the attached figures:
[0023] 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Battery module; 5. Individual battery cell;
[0024] 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0025] The embodiments of this application are described in detail below, with examples of these embodiments shown in the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0026] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; unless otherwise stated, the values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).
[0027] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.
[0028] In the description of this application, all figures disclosed herein, whether or not the words "approximately" or "about" are used, are approximate values. Each figure may vary by less than 10% or by a difference that is considered reasonable by one of the art, such as 1%, 2%, 3%, 4%, or 5%.
[0029] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0030] In this application, the order in which the steps are written does not imply a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0031] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0032] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0033] When various additives are added to the electrolyte to improve its ionic conductivity, high-temperature stability, and other properties, the viscosity of the electrolyte will increase accordingly. For example, at 25°C, the viscosity of the electrolyte can reach 3-6 mPa·s. Higher viscosity leads to poorer electrolyte flowability. During battery charging and discharging, the negative electrode active material undergoes volume expansion and contraction due to lithium ion insertion / extraction. When the negative electrode expands during charging, the electrolyte impregnated within it is squeezed out under stress. When the negative electrode contracts during discharging, due to the higher viscosity of the electrolyte, the natural reflux rate is slow, resulting in insufficient wetting of the negative electrode. As the battery continues to charge and discharge, the wettability of the electrolyte on the negative electrode gradually deteriorates, leading to a sharp drop in battery cycle performance. Furthermore, when the electrode is brittle, after repeated expansion and contraction, the negative electrode itself may break or the negative electrode active material layer may fall off, leading to further deterioration of the battery's cycle performance.
[0034] In this application, when the tensile strength of the modified styrene-butadiene rubber is 3MPa-8MPa, the binder can buffer the stress generated during the expansion of the electrode sheet, reduce the extrusion of the electrolyte, and thus significantly improve the wettability of the electrolyte on the negative electrode sheet. At the same time, when the elongation at break of the modified styrene-butadiene rubber is 150%-400%, it helps the negative electrode sheet maintain its toughness under extreme conditions, thereby significantly improving the flexibility of the electrode sheet. This allows the negative electrode sheet to undergo elastic deformation rather than brittle fracture when it undergoes significant expansion and contraction under extreme conditions, which helps maintain the structural integrity of the negative electrode sheet.
[0035] Therefore, by utilizing modified styrene-butadiene rubber with high mechanical strength and high toughness, the deformation of the negative electrode sheet during expansion is reduced, the amount of electrolyte squeezed out during expansion is decreased, and the expansion deformation is more uniform. Even if a small amount of electrolyte is squeezed out, the rapid recovery of elastic deformation provides a smooth path for electrolyte reflux. The electrolyte wettability and structural stability of the negative electrode sheet are significantly improved, and the cycle performance of the battery is significantly improved.
[0036] It is understandable that as temperature increases, the interaction between solvent and solute molecules in the electrolyte weakens, thereby reducing the electrolyte's viscosity. Therefore, the viscosity of an electrolyte decreases with increasing temperature. That is, the viscosity of the same electrolyte at room temperature is usually higher than its viscosity at high temperatures. Thus, for an electrolyte with a viscosity of 3-6 mPa·s at 25°C, its viscosity is lower at higher temperatures (such as 40°C and 50°C). Therefore, even if it is squeezed out due to the expansion of the negative electrode, its natural reflux rate will be faster, resulting in better wettability of the negative electrode.
[0037] In a first aspect, this application proposes a secondary battery comprising: a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative active material layer located on at least one side of the negative current collector, the negative active material layer including a binder, the binder including modified styrene-butadiene rubber, the modified styrene-butadiene rubber having a tensile strength of 3 MPa-8 MPa and an elongation at break of 150%-400%; and an electrolyte having a viscosity of 3 mPa·s-6 mPa·s at 25°C. This can improve the cycle performance of the battery by mitigating the degradation of the electrolyte's wettability on the negative electrode sheet during charging and discharging, thus effectively improving the battery's cycle performance.
[0038] As an example, the tensile strength of modified styrene-butadiene rubber can be 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, 5.5 MPa, 6 MPa, 6.5 MPa, 7 MPa, 7.5 MPa or 8 MPa.
[0039] When the tensile strength of the modified styrene-butadiene rubber is within the aforementioned range, it can effectively resist expansion stress, reduce the generation and propagation of cracks, maintain the pore structure of the negative electrode active material layer, and reduce the electrolyte extrusion pressure.
[0040] As an example, the elongation at break of modified styrene-butadiene rubber can be 150%, 200%, 250%, 300%, 350%, or 400%.
[0041] When the elongation at break of the modified styrene-butadiene rubber is within the aforementioned range, the adhesive can undergo elastic deformation to absorb volume changes after being subjected to force, thus avoiding brittle fracture and promoting electrolyte recirculation after rebound.
[0042] It is understandable that adhesives cannot simultaneously possess both extremely high tensile strength and extremely high elongation at break. When the elongation at break and tensile strength of modified styrene-butadiene rubber are within the aforementioned range, there are more specific materials to choose from, the manufacturing cost is lower, and it is convenient for large-scale application.
[0043] As an example, the viscosity of the electrolyte at 25°C can be 3 mPa·s, 3.5 mPa·s, 4 mPa·s, 4.5 mPa·s, 5 mPa·s, 5.5 mPa·s, or 6 mPa·s.
[0044] When the viscosity of the electrolyte is within the aforementioned range, a wider variety of additives can be selected, facilitating the improvement of electrolyte performance from multiple angles, such as ionic conductivity and high-temperature stability. However, when the electrolyte viscosity is too high, the diffusion rate of lithium ions in the electrolyte will significantly decrease, resulting in a significant drop in the battery's charge and discharge efficiency.
[0045] As an example, the tensile strength and elongation at break of modified styrene-butadiene rubber can be tested using the following method: Take 40g of adhesive or adhesive emulsion with a solid content of 40%-50%, dilute it in deionized water to obtain an adhesive solution with a solid content of 20% by weight, pour it into a mold and transfer it to an oven, bake it at 40℃ for 10 hours and at 60℃ for 4 hours in sequence, and then cut the film into dumbbell shapes for tensile testing to obtain the tensile strength and elongation at break.
[0046] Specifically, tensile strength test: sample preparation: length 50mm, width 15mm, thickness 0.3-0.5mm, tensile speed: 10mm / min, record stress-strain curve, the maximum stress is the breaking strength (i.e. tensile strength), the ratio of strain at break to original length is the breaking elongation, and the average value of three samples is taken.
[0047] As an example, the viscosity of the electrolyte can be tested using the following method: Based on Appendix D of the national standard GB / T10247-2008, a rotational viscometer is used. Specifically, an electrolyte sample is placed in a sample container, and the test is performed using a Brookfield DV2TLV rotational viscometer. At the test temperature, the shear force experienced by the rotor rotating continuously at a constant speed within the sample causes the spring to generate torque. The torque is proportional to the viscosity, thus yielding the viscosity value. Test conditions: External environment: Temperature: 15℃-28℃, Humidity: RH<80%; Internal environment: The sample container is 2 / 3 submerged in a water bath, the medium being water, which is used to maintain the temperature of the sample.
[0048] In some embodiments, the modifying groups of the modified styrene-butadiene rubber include one or more of carboxyl, amide, and ester groups. This helps to improve the mechanical strength of the binder and helps resist the stress generated during the expansion and contraction of the negative electrode sheet.
[0049] The carboxyl, amide, and ester groups in the polymer structure can be tested according to the general rules of infrared spectroscopy analysis method in the national standard GB / T 6040-2002. Specifically, the sample is pressed into a KBr pellet using the transmission method, and the KBr background blank is subtracted by the transmission method to obtain the sample test spectrum (resolution: 4 cm⁻¹). -1 Wavenumber range: 400cm -1 -4000cm -1 ).
[0050] As an example, monomers containing carboxyl, amide, or ester groups can be added during the synthesis of styrene-butadiene rubber (SBR) to induce copolymerization, thereby modifying the SBR. For instance, acrylates, acrylic acid, and acrylamide can be added to improve the adhesive properties of SBR while introducing modifying groups.
[0051] In some embodiments, the modified styrene-butadiene rubber has a weight-average molecular weight of 20,000-60,000. This results in better dispersion of the binder in the negative electrode sheet and higher mechanical strength.
[0052] As an example, the modified styrene-butadiene rubber has a weight-average molecular weight of 20,000, 30,000, 40,000, 50,000, or 60,000.
[0053] When the weight-average molecular weight of the modified styrene-butadiene rubber is within the aforementioned range, the binder can simultaneously possess high mechanical strength and low glass transition temperature, thereby achieving a large elongation at break while maintaining high tensile strength and improving the toughness of the negative electrode sheet.
[0054] In some embodiments, the glass transition temperature of the modified styrene-butadiene rubber is -30°C to -15°C. Therefore, the binder remains in a highly elastic state at the battery operating temperature, which helps to improve the toughness of the negative electrode sheet.
[0055] As an example, the glass transition temperature of the modified styrene-butadiene rubber can be -30°C, -25°C, -20°C, or -15°C.
[0056] When the glass transition temperature of modified styrene-butadiene rubber is within the aforementioned range, it can have both a lower glass transition temperature and higher mechanical strength.
[0057] In some embodiments, the mass fraction of the modified styrene-butadiene rubber in the negative electrode active material layer is 0.5%-2.5%. Therefore, the negative electrode sheet has high structural stability, and the proportion of negative electrode active material in the negative electrode active material layer is relatively high.
[0058] As an example, the mass fraction of the modified styrene-butadiene rubber in the negative electrode active material layer can be 0.5%, 1%, 1.5%, 2%, or 2.5%.
[0059] In some embodiments, the modified styrene-butadiene rubber has a swelling rate of 30%-50% in the electrolyte. This helps to improve the wettability of the electrolyte for the negative electrode sheet.
[0060] As an example, the swelling rate of the modified styrene-butadiene rubber in the electrolyte can be 30%, 35%, 40%, 45%, or 50%.
[0061] In some embodiments, the binder further includes a polyacrylic binder, wherein the mass fraction of the polyacrylic binder in the negative electrode active material layer is less than or equal to 1.5%. Thus, adding a small amount of polyacrylic binder helps to provide rigid support and enhance the structural stability of the negative electrode sheet.
[0062] As an example, the mass fraction of the polyacrylic binder in the negative electrode active material layer can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, or 1.5%.
[0063] Polyacrylic acid binders have high tensile strength and brittleness. By adding a small amount of polyacrylic acid binder to the negative electrode active material layer, the binder's ability to buffer stress expansion can be significantly enhanced, and the negative electrode sheet can also have better toughness.
[0064] In some embodiments, the negative electrode active material layer further includes carbon nanotubes, wherein the mass fraction of carbon nanotubes in the negative electrode active material layer is 0.01%-0.2%. This improves the conductivity of the negative electrode active material layer while also helping to maintain the pore channels within the negative electrode active material layer, promoting electrolyte reflux.
[0065] As an example, the mass fraction of carbon nanotubes in the negative electrode active material layer can be 0.01%, 0.05%, 0.1%, 0.15%, or 0.2%.
[0066] As an example, carbon nanotubes can be single-walled carbon nanotubes. Single-walled carbon nanotubes have high brittleness, which can suppress stress expansion of the negative electrode sheet.
[0067] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0068] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0069] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, sodium titanate, etc. The silicon-based materials include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based materials include one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0070] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0071] Typically, a secondary battery consists of a positive electrode, a negative electrode, and an electrolyte. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes and prevents short circuits between them.
[0072] [Electrolytes]
[0073] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid or gel-like.
[0074] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0075] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0076] In some embodiments, the solvent includes at least one selected from ethylene carbonate, ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0077] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0078] As an example, additives may include one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0079] [Positive electrode plate]
[0080] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0081] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0082] In some embodiments, when the battery is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art for lithium-ion batteries. As an example, the positive electrode active material may include one or more of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 )), lithium nickel cobalt aluminum oxide (such as LiNi) 0.8 Co 0.15 Al 0.05 One or more of the following: O2) and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0083] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before material addition. After charge-discharge cycles, the molar Li content changes when the positive electrode active material is applied to the battery system.
[0084] In the examples of positive electrode active materials for lithium-ion batteries in this application, the molar content of O is only a theoretical state value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0085] [Isolation membrane]
[0086] In some embodiments, the secondary battery further includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0087] In some embodiments, the material of the separator includes at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0088] In some embodiments, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0089] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0090] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0091] In some embodiments, a secondary battery may include one or more of the following: a battery cell, a battery module, and a battery pack.
[0092] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.
[0093] In some embodiments, refer to Figure 2 The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can cover the opening to close the receiving cavity. The positive electrode, negative electrode, and electrolyte may be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0094] In some embodiments, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0095] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other way. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0096] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0097] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0098] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0099] In a second aspect of this application, a method for preparing modified styrene-butadiene rubber (SBR) is provided, comprising: mixing 40-60 parts by weight of butadiene, 30-50 parts by weight of styrene, 3-8 parts by weight of acrylate, 1-5 parts by weight of acrylic acid, and 1-5 parts by weight of acrylamide, along with an emulsifier and an initiator, and heating to obtain a polymer emulsion of the modified SBR. Thus, modified SBR adhesives with superior toughness and meeting the aforementioned tensile strength and elongation at break can be obtained through emulsion polymerization.
[0100] Emulsion polymerization is a process in which monomers are dispersed in water to form an emulsion using emulsifiers and mechanical stirring, and then an initiator is added to initiate the polymerization of the monomers.
[0101] Emulsifiers are substances that can transform immiscible oils and water into emulsions that are difficult to separate. Emulsifiers are usually surfactants that combine the properties of both hydrophilic polar groups and hydrophobic (lipophilic) nonpolar groups.
[0102] An initiator is a substance that can initiate a polymerization reaction of monomers. For example, a free radical initiator refers to a class of compounds that are easily decomposed into free radicals (i.e., primary free radicals) by heat, and can be used to initiate free radical polymerization and copolymerization reactions of alkene and diene monomers.
[0103] In some embodiments, the emulsifier includes at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfate, sodium laurylate, sodium stearate, and sodium palmitate.
[0104] In some embodiments, the initiator includes at least one selected from persulfate initiators, acyl peroxide initiators, and azo initiators. Specifically, persulfate initiators include at least one selected from potassium persulfate and ammonium persulfate; acyl peroxide initiators include at least one selected from benzoyl peroxide and di-n-octanoyl peroxide; and azo initiators include at least one selected from azobisisobutyronitrile and dimethyl azobisisobutyrate.
[0105] In some embodiments, the modified styrene-butadiene rubber in the polymer emulsion has a Dv50 particle size of 150 nm to 300 nm. This helps to improve the dispersion uniformity of the modified styrene-butadiene rubber.
[0106] It is understandable that the modified styrene-butadiene rubber actually used is usually an agglomeration of multiple polymer particles. Therefore, the particle size of the modified styrene-butadiene rubber in the negative electrode active material layer will be larger than that in the polymer emulsion.
[0107] In some embodiments, acrylic acid introduces carboxyl groups into styrene-butadiene rubber, which can improve the adhesive properties; acrylamide introduces amide groups into styrene-butadiene rubber, which can act as reactive groups to promote polymerization; acrylate introduces ester groups into styrene-butadiene rubber, which can adjust the flexibility and crosslinking properties of the adhesive.
[0108] In some embodiments, increasing the amount of butadiene in emulsion polymerization can increase the flexibility of the binder; increasing the amount of styrene can increase the strength of the binder.
[0109] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.
[0110] In a third aspect, this application proposes an electrical device including the aforementioned secondary battery. Therefore, this electrical device possesses all the features and advantages of the aforementioned secondary battery, which will not be repeated here.
[0111] The aforementioned battery cells or battery packs can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0112] As the electrical device, a single battery cell or a battery pack can be selected according to its usage requirements.
[0113] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0114] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0115] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0116] Example 1
[0117] 50 parts butadiene, 40 parts styrene, 3.5 parts butyl acrylate, 1.5 parts (meth)acrylic acid, and 2.5 parts acrylamide were subjected to emulsion polymerization. This emulsion polymerization also included 1 part emulsifier (a mixture of sodium dodecyl diphenyl ether disulfonate and sodium dodecyl sulfonate in a 3:1 mass ratio), 0.5 parts molecular weight regulator (dodecyl mercaptan), and 1 part initiator (ammonium persulfate). The aforementioned substances were mixed in deionized water to ensure a total mass fraction of approximately 40%. The polymerization temperature was 65°C, the polymerization time was 12 hours, and the stirring speed was 500 rpm. The reaction was completed to obtain a modified styrene-butadiene rubber adhesive.
[0118] The tensile strength and elongation at break of the modified styrene-butadiene rubber in Example 1 were tested. The test results showed that the tensile strength was 3 MPa and the elongation at break was 150%.
[0119] Preparation of the negative electrode sheet: 96 parts graphite, 1 part conductive carbon black, 2 parts modified styrene-butadiene rubber binder, and 1 part carboxymethyl cellulose were dissolved in deionized water and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry was then prepared at a concentration of 160 mg / 1540.25 mm. 2 The load is uniformly coated onto the negative electrode current collector copper foil once or multiple times, and then dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0120] The separator is made of porous polyethylene membrane.
[0121] Preparation of positive electrode: LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) material, conductive agent carbon black, PVDF, and N-methylpyrrolidone (NMP) were mixed evenly at a weight ratio of 96.9:2:1:21 to obtain a positive electrode slurry; then, the positive electrode slurry was mixed at 260 mg / 1540.25 mm. 2 The loading amount is uniformly coated on the positive current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet.
[0122] Electrolyte: Equal volumes of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed to obtain an organic solvent. LiPF6 is then dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L and a viscosity of 4 mPa·s.
[0123] Battery assembly: The positive electrode, separator, and negative electrode are stacked and wound in sequence and hot-pressed to form a battery cell; the battery cell is placed in an outer packaging, the electrolyte prepared above is added, and after processes such as encapsulation, standing, formation, and aging, a battery cell is obtained.
[0124] The differences between the remaining embodiments and comparative examples and Embodiment 1 are shown in Table 1.
[0125] Table 1
[0126]
[0127]
[0128] The aforementioned battery was subjected to the following tests, and the test results are shown in Table 2:
[0129] (1) Negative electrode thickness rebound rate test
[0130] At 25℃, the battery was charged to 4.3V at a rate of 0.5C, and then charged at a constant voltage of 4.3V until the current was less than or equal to 0.05C. After that, it was left to stand for 5 minutes. At this time, the battery was in a fully charged state. Then, the cycled battery was disassembled in a dry room to obtain the negative electrode sheet after full charge cycle. The thickness of the electrode sheet at full charge was tested. Compared with the thickness of the negative electrode sheet after cold pressing, the increase in thickness was the full charge rebound rate of the electrode sheet.
[0131] (2) Cyclic & Cyclic Expansion Force
[0132] Take a fresh battery cell, with three steel clamps, install a KEPRE pressure sensor to monitor the expansion force, and set the preload force to 3000N;
[0133] The cycle process is as follows: Under a constant temperature environment of 25℃, the prepared battery is charged at a constant current of 0.5C to the upper limit voltage of 4.5V, and then charged at a constant voltage at the upper limit voltage until the current is ≤0.05C. After standing for 5 minutes, it is discharged at a constant current of 1C to the lower limit voltage of 2.5V. This is one cycle of charge and discharge. Repeat the above steps until the cycle capacity retention rate reaches 80% SOH, and read the number of cycles and the cell expansion force at this time.
[0134] Table 2
[0135]
[0136] Test results show that:
[0137] While using only polyacrylic acid binders effectively suppresses electrode rebound, their inherent brittleness leads to microscopic fracture of the negative electrode during cycling at the same dosage, resulting in poor cycle performance. When the modified styrene-butadiene rubber (SBR) has a tensile strength of 3-8 MPa and an elongation at break of 150%-400%, it significantly improves the electrode's flexibility, buffering the stress generated during negative electrode expansion. This allows the negative electrode to undergo elastic deformation rather than brittle fracture even under extreme conditions of significant expansion and contraction, helping to maintain the structural integrity of the negative electrode, reducing electrolyte extrusion, and thus significantly improving electrolyte wettability and cycle performance.
[0138] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A secondary battery, characterized in that, include: A negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative active material layer located on at least one side of the negative current collector, the negative active material layer comprising a binder, the binder comprising modified styrene-butadiene rubber, the modified styrene-butadiene rubber having a tensile strength of 3MPa-8MPa and an elongation at break of 150%-400%; The electrolyte has a viscosity of 3 mPa·s to 6 mPa·s at 25°C.
2. The secondary battery according to claim 1, characterized in that, The modifying groups of the modified styrene-butadiene rubber include one or more of carboxyl groups, amide groups, and ester groups.
3. The secondary battery according to claim 2, characterized in that, The modified styrene-butadiene rubber has a weight-average molecular weight of 20,000 to 60,000.
4. The secondary battery according to claim 2 or 3, characterized in that, The glass transition temperature of the modified styrene-butadiene rubber is -30℃ to -15℃.
5. The secondary battery according to any one of claims 2-4, characterized in that, The modified styrene-butadiene rubber in the negative electrode active material layer has a mass fraction of 0.5%-2.5%.
6. The secondary battery according to any one of claims 2-4, characterized in that, The modified styrene-butadiene rubber has a swelling rate of 30%-50% in the electrolyte.
7. The secondary battery according to any one of claims 2-6, characterized in that, The binder further includes a polyacrylic binder, wherein the mass fraction of the polyacrylic binder in the negative electrode active material layer is less than or equal to 1.5%.
8. The secondary battery according to any one of claims 1-7, characterized in that, The negative electrode active material layer also includes carbon nanotubes, and the mass fraction of carbon nanotubes in the negative electrode active material layer is 0.01%-0.2%.
9. A method for preparing modified styrene-butadiene rubber, characterized in that, include: 40-60 parts by weight of butadiene, 30-50 parts by weight of styrene, 3-8 parts by weight of acrylate, 1-5 parts by weight of acrylic acid and 1-5 parts by weight of acrylamide, as well as emulsifier and initiator are mixed and heated to obtain the polymer emulsion of the modified styrene-butadiene rubber.
10. The method according to claim 9, characterized in that, The modified styrene-butadiene rubber in the polymer emulsion has a Dv50 particle size of 150nm-300nm.
11. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 1-8.